Violating organizational and social norms in the workplace: a correlational study in the nursing context - Zaghini, Francesco; Biagioli, Valentina; Caruso, Rosario; Badolamenti, Sondra; Fida, Roberta; Sili, Alessandro (La Medicina del Lavoro, 2017)
Objectives: The aim of this study was to examine, in a sample of nurses, the relationships between the organizational context variables (i.e., workload, interpersonal conflicts, organizational constraints), the burnout, the moral disengagement, and the counterproductive work behaviors (CWB), within their clinical work settings. Methods: A descriptive, correlational study was conducted in a sample of 347 nurses working in different clinical settings in a big university hospital in Central Italy. A self-report questionnaire was used for data collection, using several scales to assess different variables related to the organisational context, the burnout, the interpersonal strain, the moral disengagement, and the CWB. Results: The clinical context was found to influence nurses’ organizational wellbeing, which in turn was found to foster CWB. Nurses working in outpatients settings and in day hospitals were those who reported the lowest CWB, in comparison with nurses working in the Emergency Department and in the General Medicine Units. Conclusions: Findings of this study are important for nursing professional chiefs and for any professional involved in the promotion of workers’ wellbeing. Our study findings highlight how the clinical work setting and the organizational context variables can lead to CWB. Researchers and managers should keep these aspects in high consideration due to their influence on the quality of the care delivered.